49‐2: Invited Paper: Stretchable Passive Matrix LED Display with Thin‐Film Based Interconnects. Issue 1 (May 2016) - Verplancke, Rik; Cauwe, Maarten; Van Put, Steven; Smits, Edsger C. P.; Kusters, Roel; van Heck, Gert; van den Brand, Jeroen; Murata, Mitsuhiro; Ohmae, Hideki; Tomita, Yoshihiro; Nakata, Hideki; Vanfleteren, Jan; et al.
Abstract : In this contribution, a conformable 64×45 RGB light‐emitting diode (LED) matrix is presented. A design concept of stretchable electronics is used: non‐stretchable polymer islands host rigid LEDs and are interconnected by horseshoe shaped metallic conductors, which are able to deform together with an elastomeric substrate. Thin‐film metallization is used to enable a pixel pitch of 1 mm, while polyimide is used to realize the non‐stretchable islands, but also to support the meandering conductors. The design of the stretchable interconnections has been optimized with respect to their mechanical and electrical performance. Thermoplastic polyurethane is introduced at a final stage of the fabrication process to ensure its compatibility with conventional thin‐film processing. A passive matrix addressing scheme is used to drive the LED matrix. At a supply voltage of 10 V, the brightness of the display reaches up to 700 cd/m 2 .